Still legacy application
vbnet
For x = 1 To y
q(x, y + 1) = q(x, y + 1) + p(I, J) * ay(I)
For z = 1 To y
q(z, x) = q(z, x) + p(I, z) * p(I, x)
Next z
Next x
I immediately refactored the I and J to be lowercase.
This is an archive of the posts published to LessThanDot from 2008 to 2018, over a decade of useful content. While we're no longer adding new content, we still receive a lot of visitors and wanted to make sure the content didn't disappear forever.
Still legacy application
vbnet
For x = 1 To y
q(x, y + 1) = q(x, y + 1) + p(I, J) * ay(I)
For z = 1 To y
q(z, x) = q(z, x) + p(I, z) * p(I, x)
Next z
Next x
I immediately refactored the I and J to be lowercase.